(untitled) (Actual Problems of Mind, 2022)
The article discusses the problem of the compatibility of Descartes’s doctrine of interactionist substance dualism with his claims about the law of the conservation of the quantity of motion, about the way God maintains the world in existence, and about minds and bodies having only properties that are modes of thinking or extension respectively. The case is made that although there seem to be prima facie conflicts, they can be neutralised as merely apparent. The position that mental states cause some motions in the brain is consistent with Descartes’s postulation of the existence of the law of conservation of the quantity of motion, insofar as it derives from God’s immutability whereas souls are not immutable, as well as with the laws of conservation established by Newtonian physics, insofar as they don’t prohibit purely redistributive changes and are established only for physical interactions. Descartes’s interactionism does not conflict with his statements about the way God maintains the world in existence, if the latter are construed in the sense that God preserves motion in the world by preserving the laws of nature, and the conservation of the world by God is a continuation of the initial act of creation. The principle that all properties of a substance are modes of its main attribute agrees with substance dualism and interactionism, if we admit that Descartes’s ontology of the world includes, besides substances of two kinds with their main attributes and modes of those attributes, something more ‒ irreducible sue generis entities, such as the substantial union of body and soul and/or psychophysical laws of nature.